A new synonym and new records of Tychiini (Coleoptera, Curculionidae) from Madeira Archipelago and Selvagens Islands - Caldara, Roberto (2022)
Tychius bicolor Brisout, 1862 and Sibinia arenariae Stephens, 1831 are reported from the Archipelago of Madeira, respectively Madeira and Porto Santo, for the first time. Two additional specimens of T. filirostris Wollaston, 1854, known previously from only two specimens from Porto Santo, were examined. Following the study of these specimens and others from the Canary Islands (Tenerife, La Palma) and Selvagen Pequena, T. colonnellii Caldara, 1991 from Tener ife is proposed as a junior synonym of T. filirostris. The archipelagos of Macaronesia (Madeira, Azores, Selvagens, Canary Islands and Cape Verde Islands) represent one of the richest areas for endemic species in Europe. Although some genera, especially of beetles, have there under gone considerable radiation, the tribe Tychiini, which in the Palaearctic region comprises about 250 species, is poorly represented in Macaronesia. Its archipelagos harbour only 13 species belonging to the only two genera known in the Palaearctic region, Tychius Germar, 1817 and Sibinia Germar, 1817. Among these species only three are endemic, the others being mainly of European, Mediterranean and North African distribution. Up to now, in the Macaronesian archi pelagos Tychiini are unknown from the Cape Verde Islands and Selvagens, whereas the group has its largest number of species in the Canaries (10), followed by the Azores (2) and Madeira (1). The only species of Tychiini reported so far from Madeira is T. filirostris Wollaston, 1854, which was only known from two females collected on the island of Porto Santo and is seemingly endemic to this archipelago. This study reports new material of T. filirostris and two new species records from the Madeira archipelago: Tychius bicolor Brisout, 1862 from Madeira and Sibinia arenariae Stephens, 1831 from Porto Santo. In addition, examination of Wollaston’s holotype and two new specimens of T. filirostris and their comparison with the holotype, paratypes and other specimens of T. colonnellii Caldara, 1991 from the Canary Islands (Tenerife, La Palma) and Selvagen Pequena (new record) have led to the establishment of a new synonymy. Thus, T. colonnellii, considered endemic to the Canary Islands archipelago, is sunk into synonymy with T. filirostris. A checklist of all the species of Tychiini present in the archipela gos of Macaronesia is presented.